Electrical and photoresponse properties of Al/p-CuFeO2/p-Si/Al MTCOS photodiode - Gupta, R. K.; Cavas, M.; Al-Ghamdi, Ahmed A.; Gafer, Z. H.; El-Tantawy, F.; Yakuphanoğlu, Fahrettin (Pergamon-Elsevier Science Ltd, 2013)
A p-type transparent semiconductor, CuFeO2 was synthesized by sol gel method to fabricate metal/transparent conducting oxide-semiconductor (MTCOS) Schottky photodiode. The optical and electrical properties of the CuFeO2 film and Al/p-CuFeO2/p-Si/Al diode were studied. The optical band gap of the CuFeO2 film was calculated using optical data and was found to be 2.82 eV. The diode exhibits a photoconducting behavior with a high photosensitivity value of 1.31 x 10(3) under 100 mW/cm(2). The ideality factor and barrier height of the diode were obtained to be 1.67 +/- 0.2 and 0.55 +/- 0.01 eV, respectively. The interface states have been used to explain the results obtained in this study. It is evaluated that MTCOS photodiode can be used for optoelectronics applications. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: CuFeO2; Band gap; Schottky diode; Sol-gel; Junction properties; Capacitance